2007
DOI: 10.1590/s0102-05362007000400003
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de alface crespa minimamente processada armazenada sob refrigeração em dois sistemas de embalagem

Abstract: Quality of fresh-cut crisphead lettuce stored under refrigeration and two packaging systemsMinimal processing usually causes quality loss, reduces shelflife, and promotes sensory attributes alterations. The occurrence of browning in the midrib of fresh-cut lettuce is commonly observed and is associated with cell tissue disrupture, putting in contact enzymes and their respective substrates. Chemical, physical, and biochemical quality of fresh-cut crisphead lettuce stored under refrigeration and two different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
5
0
8
Order By: Relevance
“…Such a decrease in acidity is related to the enzymatic reactions that occur in minimally processed food. Mattos et al (2007) found the same behavior in minimally processed lettuce. The values of the ASC were determined for the lettuce packed in different treatments (Figure 3,.…”
Section: Physicochemical Analysismentioning
confidence: 53%
See 2 more Smart Citations
“…Such a decrease in acidity is related to the enzymatic reactions that occur in minimally processed food. Mattos et al (2007) found the same behavior in minimally processed lettuce. The values of the ASC were determined for the lettuce packed in different treatments (Figure 3,.…”
Section: Physicochemical Analysismentioning
confidence: 53%
“…It was observed that there was an increase in the values of L* for the treatments with biodegradable films and a decrease for the PVC treatment at 4 days of storage; at this stage, the values of C* had already increased in the lettuce packaged in films with PVC, remained the same in EOLM films, and declined in EOCP and WEO films. Mattos et al (2007) found that minimally processed lettuce presented a lower lightness value than lettuce in whole leaves. These authors concluded that the higher activity of peroxidase and polyphenol oxidase in cut leaves was responsible for the results.…”
Section: Analysis Of Colormentioning
confidence: 92%
See 1 more Smart Citation
“…Em repolho, na colheita, os valores de AT (0,2) estão abaixo dos reportados por outros autores (0,36-0,91), enquanto que para o mix de folhas (0,2) são semelhantes aos apresentados na alface crespa armazenada sob refrigeração, podendo ser reportadas como hortaliças de baixa acidez, assim como o kit yakissoba (0,3). 26,23 A manutenção dos valores de AT pode estar relacionada à redução da atividade respiratória em decorrência da redução dos níveis de O 2 e concentração de CO 2 no interior das embalagens, promovendo manutenção dos ácidos orgânicos.…”
Section: Tratamentounclassified
“…In Brazil, as in many other countries, lettuce (Lactuca sativa L.) is one of the most consumed leafy vegetables, attributable to year round availability, low cost and nutritional factors (Abreu et al, 2010;Mocelin and Figueiredo, 2009;WHO et al 2008;Mattos et al, 2007). The Brazilian lettuce cultivation system is predominantly done in open fields, which are located for the most part at urban surroundings.…”
Section: Introductionmentioning
confidence: 99%